Web-based application recitation in prayer for OKU / Syakirah Suhaimi - Suhaimi, Syakirah (2022)
Currently, there are many applications that is being used in the education sector, may it be mobile application, web-based application as well as other types of application. As a matter of interest, the OKU learners are also a group of people which has their own interest in using the technology such as web-based application or mobile application towards learning. But some application might not be suitable for this group of people which is slower in the learning process. This paper describes about the recitation in prayer application among the OKU learners in learning to recite in their prayer with the correct pronunciation. This work presents the solution for the above scenario, a web-based application is intended to be develop. This application will help the OKU learners to learn better in their recitation for prayer according their pace. This application implements multimedia elements such as audio and image to make the website useful for the users of the website hence the objective of this project can be achieved, particularly to design and develop an application based on the learning methods obtained by discussing the learning methods which are more suitable for the special learners. The learning method that is being used in this project is the Al-Baghdadi technique which is one of the techniques in learning the Al-Quran and this project has found out that this technique was more suitable for the intended user of the application. In the development process, Sublime Text version 3 was used and this application was linked with the XAMPP which is a web server. It provides the connection between the text editor with the web browser. This application has also been tested among one of the OKU learners which the result shows an average percentage of 68% is obtained after calculation was made with reference to the System Usability Scale (SUS) Score. By having the web-based application, it is hope that the intended user can gain benefit after using the website.